ROLE OF SINTERING IN SNOW CONSTRUCTION. - Ramseier,Rene O. (1967)
The mechanism of sintering and the effect of compaction on snow is discussed. Examples of possible snow runway construction using processed snow for Site II, Greenland, and McMurdo Sound and Amundsen-Scott South Pole Station, Antarctica, are given. From theory and the examples discussed, it is concluded that snow runways capable of handling large aircraft can be constructed in any polar or temperate region with enough snow and temperatures below the melting point for a sustained period. (Author)